Effectiveness of Using Jendela Pontianak Integrasi (JEPIN) Application toward Developing Smart City in Siantar Hilir North Pontianak District - Anggraini, Yesi Putri; Elyta, Elyta; Rohilie, Haunan Fachry (International Journal of Multidisciplinary Approach Research and Science, 2024)
This article analyzes the effectiveness of using the Pintu Pontianak integration application in realizing a Smart City in the Siantan Hilir Village area, North Pontianak District. Jendela Pontianak Integrasi (JEPIN) implements the Smart City concept adopted by the Pontianak City government to facilitate public access to information and public services. Even though it is aimed at people who actively use technology, several obstacles hinder the effectiveness and acceptance of this application. Among them are the complexity of features and terms in applications that still need to be fully understood by the public and a need for more awareness of the benefits of the innovative city concept. Socialization efforts carried out by the government have yet to fully increase public understanding and interest in the JEPIN application. Therefore, concrete steps such as simplifying the user interface, increasing socialization, and regular evaluation are needed to ensure the success and broader acceptance of the JEPIN application. In this way, JEPIN can be a more effective tool in supporting Pontianak City's Smart City vision and improving the quality of public services for the community.